2004
DOI: 10.1111/j.1400-0952.2004.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical catchment changes and temporal impact on sediment of the receiving basin, Port Jackson, New South Wales

Abstract: Port Jackson (Sydney Harbour) is a major deep-water estuary on the central New South Wales coast and is surrounded by a highly urbanised and industrialised catchment. Concentrations of trace metals and organochlorine pesticide residues are high in sediment in the upper reaches of the estuary. Historical fluxes of contaminants into the estuary were determined by radio-isotopic dating of 12 sediment profiles in nine highly contaminated embayments. The onset of contamination in estuarine sediment was correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…Retrograde analysis of shoreline land use was undertaken by geo-referencing historical maps for the periods 1788, 1850, 1892, 1936, 1943, 1978 and 2010 augmented by aerial photography for years 1936-2010. Time horizons were chosen depending on data availability and phases of industrialisation identified by previous studies (Links 1998;Taylor et al 2004). Land use maps were constructed to determine historic changes in the extent of shoreline industry and to identify coring sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrograde analysis of shoreline land use was undertaken by geo-referencing historical maps for the periods 1788, 1850, 1892, 1936, 1943, 1978 and 2010 augmented by aerial photography for years 1936-2010. Time horizons were chosen depending on data availability and phases of industrialisation identified by previous studies (Links 1998;Taylor et al 2004). Land use maps were constructed to determine historic changes in the extent of shoreline industry and to identify coring sites.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier radio-isotopic dating ( 210 Pb; 134 Cs) of 12 sediment cores (Taylor et al 2004) and load calculations indicated that present-day stormwater discharges accounted for onlỹ 10 % of the total mass of metals in estuarine sediment. These data suggested that either metal loads were substantially higher in the past, or that there existed a large alternative source of metals other than stormwater, possibly industrial sources.…”
Section: Introductionmentioning
confidence: 99%
“…Poor sediment quality within these sub-estuaries is likely attributed to historical catchment use, which includes history of intense industrial activity and legacy contamination. Earliest industrial activity in Sydney was located close to the present CBD and to the east of Darling Harbour (Taylor et al 2004;Birch et al 2015a). Three bays (Blackwattle, Rozelle and Cockle Bays) were the first to be urbanised with the establishment of several metal foundries, tanneries and other small industries during the 1800s (Taylor et al 2004;Links 1998).…”
Section: Estuarine Conditionmentioning
confidence: 98%
“…Earliest industrial activity in Sydney was located close to the present CBD and to the east of Darling Harbour (Taylor et al 2004;Birch et al 2015a). Three bays (Blackwattle, Rozelle and Cockle Bays) were the first to be urbanised with the establishment of several metal foundries, tanneries and other small industries during the 1800s (Taylor et al 2004;Links 1998). Recent research has associated declining metal concentrations in modern, surficial sediment mantling in Sydney estuary (Birch et al 2013) with the decline of shoreline industry (Birch et al 2015a).…”
Section: Estuarine Conditionmentioning
confidence: 98%
“…The impacts of dredging activity are worse in port areas because the marine environment of bays and estuaries, where the ports are located, usually function as receptors for contaminants from industrialization and urbanization of the adjacent coastal zone (Cundy et al, 2003;Taylor et al, 2004). Thus, disturbing sediments in these areas often results in high levels of contamination, especially from heavy metals and hydrocarbons (Yeager et al, 2010).…”
Section: Introductionmentioning
confidence: 99%